Preparation of lead, copper and mercury adsorbent from sago waste : effect of adsorbent ph - Angeline, Gowbei (Universiti Malaysia Sarawak, UNIMAS, 2008)
Sago processing waste, which is both a waste and a pollutant, were used to adsorb lead, mercury and copper ions from solution. The effects of adsorbent’s pH and types of sago wastes on the sorption process were examined. The most effective pH range for adsorbent was found to be 4.5 to 6 for mercury for both wastes. pH 4.5 was found to be effective for the removal of lead by coarse waste but the removal of lead by fine waste was very poor. For copper removal, the sorption was found to be poor for both type of activated carbon prepared. Sago coarse waste in this study found to be a better adsorbent compared to sago fine waste because it could adsorb two types of metal, which were Pb and Hg out of the three metals in this study whereas fine waste adsorbent could only adsorb Hg out of the three metal.